Kreativitas Guru Pendidikan Agama Islam dalam Pengembangan Bahan Ajar di Madrasah Aliyah Muhammadiyah 2 Yanggong - Lailatul Munawaroh (Social Science Academic, 2023)
Creativity is the key to the effectiveness of a complete learning process and to achieve optimal learning and educational goals. The purpose of this study was to examine the development of teaching materials used by teachers in learning at Madrasah Aliyah Muhammadiyah 2 Yanggong, teaching materials as a conceptual support tool to optimize the teaching and learning process towards the expected goals. To achieve this goal, this study uses a qualitative approach. Data collection techniques were carried out by interviews, observation and documentation studies. Data analysis methods include data reduction, data display, and verification. The research subjects were school principals, vice principals and teachers. The results obtained illustrate that (1) teachers who develop teaching materials in the PAI learning process at Madrasah Aliyah Muhammadiyah 2 Yanggong generally have creativity. This form of creativity is reflected in the variety of educational materials developed and the results. own creations provided by the school library, purchased from retail stores, approved by relevant agencies, or downloaded from various existing websites. Instructional materials used with intensity of use and quality that are different from the teaching materials themselves, for example. books, pictures, brochures, worksheets, models, tapes and CDs; and (2) the teacher's efforts in developing teaching materials are realized by trying to plan and creatively create and use teaching materials needed within the framework of Islamic religious education in accordance with the respective materials and sub-materials